Validity and reliability test to analyze effects of environment and managerial characteristics on small industries performance - Hanafi, Imam; Fitrianto, Anwar (Hikari, 2014)
We conducted validity and reliability tests prior to the data collection and analysis. The tests are known to be very important in a research in which its data source is obtained using questionnaires. In this research we found that the sets of questions which are representing operational environment, internal environment, managerial characteristics, cost advantage strategy, differentiation strategy, financial and non-financial performance, valid and reliable.